2015
DOI: 10.1016/j.revmed.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Uvéites et biothérapies

Abstract: Biotherapies used in clinical practice for the treatment of uveitis include monoclonal antibodies and fusion proteins (anti-TNFα, anakinra, tocilizumab and rituximab), interferons (IFN) and intravenous immunoglobulins (IVIg). IFN is capable of inducing prolonged remission and continued after his discontinuation, in 20-40% of patients. Side effects (flu-like, psychological effects) limit its use in practice. Anti-TNFα (infliximab and adalimumab) represents an attractive alternative therapeutic in severe uveitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 88 publications
0
1
0
2
Order By: Relevance
“…In contrast, other studies found a preeminence of immunosuppressive agents (Mycophenolate mofetil, Ciclosporine A, Methotrexate, and Azathioprine) over corticosteroids alone, while others were more reserved [26,30]. Finally, biological therapies are used in non-infectious uveitis including VKH disease [31] but the treatment length in VKH disease is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies found a preeminence of immunosuppressive agents (Mycophenolate mofetil, Ciclosporine A, Methotrexate, and Azathioprine) over corticosteroids alone, while others were more reserved [26,30]. Finally, biological therapies are used in non-infectious uveitis including VKH disease [31] but the treatment length in VKH disease is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Le certolizumab pégol est administré à la dose de 200 mg tous les 15 jours par voie sous-cutanée avec une première injection de 200 mg×2 (41). * Immunoglobulines intraveineuses (IgIV) Les IgIV sont des préparations thérapeutiques d'IgG humaines, à partir d'un pool de plasma de plus de 1000 individus sains (43). Les IgIV sont administrées par la voie intraveineuse à la dose de 0,8 à 2 g/kg répartis sur un à cinq jours.…”
Section: * Tocilizumabunclassified
“…Les IgIV sont administrées par la voie intraveineuse à la dose de 0,8 à 2 g/kg répartis sur un à cinq jours. En cas d'efficacité et de bonne tolérance, les cures d'IgIV sont répétées quatre à six fois, toutes les quatre semaines (43). Rituximab (RTX) Le RTX est un anticorps monoclonal dirigé contre l'antigène CD20 des lymphocytes B matures.…”
Section: * Tocilizumabunclassified